Prevalence and factors associated with preventable under-five mortality in Kelantan, Malaysia from 2018-2021 - Mazlan, Farah Munirah Mior (2023)
Background of study: The Sustainable Development Goals (SDG) target to end the preventable deaths of newborns and children under-five years of age by 2030, with all countries aiming to reduce under-five mortality to at least as low as 25 per 1,000 live births. Under-five Mortality Rates is an important indicator for child health and well-being, and reflects the social and economic development. Objective: The aim of the study was to determine the prevalence, causes and factors associated with preventable under-five mortality in Kelantan from 2018-2021. Methodology: A cross sectional study was conducted between December 2022 till June 2023 among under-five deaths from ten districts in Kelantan notified to Kelantan State Health Department from 2018 to 2021. The study used secondary data derived from Stillbirth and Under-five Notification System and Stillbirth and Under-five Mortality Investigation Form. A simple random sampling method using Microsoft Excel was applied to select 904 deaths from all cases. The descriptive, simple logistic regression and multiple logistic regression analysis were applied. Results: A total of 904 under-five deaths who fulfill the inclusion and exclusion criteria were studied. This study showed that 46.7% of under-five deaths was preventable. Further analysis showed that preventable under-five deaths was significantly associated with maternal aged 14-19 (Adj. OR 2.69, 95% CI: 1.24,5.83; p=0.012), household income less than RM3000 (Adj. OR 1.55, 95% CI 1.05,2.31; p=0.030), child age (Adj. OR 0.19, 95% CI 0.12,0.31; p <0.001), child without comorbidities (Adj. OR 3.26, 95% CI 2.37,4.49; p<0.001) and shortfall of quality of care (Adj. OR 7.02, 95% CI 4.23,11.65; p<0.001). Conclusion: The number of preventable under-five deaths is substantiate and it was associated with family related factor, child related factor and health service related factor. Factors such as maternal aged 14-19, household income less than RM3000, child age, child without comorbidities and shortfall of quality of care were significantly associated with preventable under-five deaths. Recognition of these associated factors hence may guide healthcare providers for improvisation of strategy and future intervention in order to end the preventable under-five deaths and achieve the SDG by 2030.